Effects of Caper (Capparis Spinosa) and Acetic Acid on Lipid Profile and Protein Concentration in the Serum of Albino Mice - Alrawi, Saad Thabit Jassim; Humide, A. O.; Al- jeboori, Mohanad D. (Iraqi Journal of Science, 2021)
This study aimed to determine the effects of alcoholic and aqueous extracts of caper (Capparis Spinosa) and acetic acid on serum lipid profile and proteins levels in mice. Sixty adult mice with an average weight of 24±4 g grams were divided into four groups (15 mice for each). The first group (G1) was administrated daily with an oral dose of caper alcoholic extract (200 mg/kg) for 28 days. The second group (G2) was administrated daily with an oral dose of caper aqueous extract (200 mg/kg) for 28 days. The third group (G3) was administrated with a daily dose of 10 % acetic acid (2 ml/kg) for 28 days. The fourth Group (G4) was administrated daily with distilled water for 28 days, as a control group. The levels of lipid profile parameters, blood urea, total protein, albumin, and globulin were determined. The results showed a significant reduction (P≤0.05) in cholesterol and triglyceride levels in mice that were treated with alcohol or aqueous extracts of caper compared with acetic acid-treated and control groups. On the other hands, the results showed a significant reduction (P≤0.05) of blood urea levels in mice that were treated with alcohol or aqueous extracts of caper compared with acetic acid-treated and control groups. While the results recorded non-significant differences in the levels of total protein, albumin, and globulin in the serum of mice of different treatment groups. From the results, it can be concluded that caper has protective effects via acting to improve the lipid profile and urea level in the blood of mice.